2006
DOI: 10.1111/j.1744-6198.2006.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Moving From a Culture of Blame to a Culture of Safety in the Nursing Home Setting

Abstract: Nurse leaders can create an environment in which every member of the team feels a responsibility and an ability to insure that residents are safe by improving communication and participation in decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 22 publications
0
53
0
5
Order By: Relevance
“…Whilst not always made explicit in the variables, organisational leadership often emerges as a central factor in the outcomes of interventions, obstructing or diffusing intended effects through lack of effective leadership [51], instability [17,35,38], incoherence [52] or inadequate resources [53]. Organisational investment in leadership roles through training and supportive systems is seen to be highly cost effective in the improvement of outcomes across the spectrum and is strongly recommended [16,20,43,54].…”
Section: Resultsmentioning
confidence: 99%
“…Whilst not always made explicit in the variables, organisational leadership often emerges as a central factor in the outcomes of interventions, obstructing or diffusing intended effects through lack of effective leadership [51], instability [17,35,38], incoherence [52] or inadequate resources [53]. Organisational investment in leadership roles through training and supportive systems is seen to be highly cost effective in the improvement of outcomes across the spectrum and is strongly recommended [16,20,43,54].…”
Section: Resultsmentioning
confidence: 99%
“…The first factor, effective nursing leadership, is said to exist when high-level nursing administrators and mid-level nurse managers encourage RNs and licensed support staff to communicate openly about the understandings and misunderstandings encountered during mundane care-giving activities, to engage in collective problem identification and resolution, and to strive continuously to build collaborative teamwork practices [33, 35, 36]. Moreover, inclusive nursing leadership is indicated by the consistent presence of nurse managers at the unit level, coupled with a demonstration of patience, empathetic listening and respect for the entrenched habits of the frontline nursing-support staff, as well as managerial skill in allocating equitable workloads among the nursing staff [6, 3739].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some have suggested that the shift from a culture of blame to a culture of safety may be even more difficult in the NH setting because of already-stretched resources, limited nursing leadership, high staffing turnover, and the current adversarial regulatory environment (39,81). Yet a number of types of adverse events in NHs are affected by multiple inputs and require a complex organizational approach to address them.…”
Section: Safety As a Quality Issuementioning
confidence: 99%
“…Despite the enthusiasm for a culture of safety, it is the culture of blame, promulgated by internal policies, the legal system, and regulatory bodies, that continues to permeate the health care industry. Fear of chastisement and the perception of error reporting as a personal attack prevent NH staff from openly discussing resident safety issues (33,81). The threat of legal action, both civil liability and criminal prosecution, and the potential for negative publicity for the NH similarly discourage honest discussion among stakeholders (39).…”
Section: Barriers To Improvementmentioning
confidence: 99%
See 1 more Smart Citation